(Pentafluoropropionato-κO)tetrakis(trimethylphosphine oxide-κO)copper(II) pentafluoropropionate - Szymańska, Iwona B. (International Union of Crystallography, 2011)
The title compound, [Cu(C(3)F(5)O(2))(C(3)H(9)OP)(4)](C(3)F(5)O(2)), comprises a cationic Cu(II) complex and a disordered pentafluoropropionate counter-ion. The metal atom has a distorted square-pyramidal coordination environment formed by four O atoms originating from trimethylphosphine oxide molecules and the remaining one belonging to the monodentate pentafluoropropionate anion, which is situated in the basal plane of the pyramid. The molecules are held together in the crystal by a net of weak C—H⋯O and C—H⋯F hydrogen bonds. The counter anion is disordered over two sets of sites in a 0.629 (5):0.371 (5) ratio.